Analysis of bearing outer race defects in induction motors - Irfan, M. (IEEE Computer Society, 2014)
The literature review presents the various kind of existing condition monitoring methods and highlights the need for an economical intelligent fault diagnosis system. This paper demonstrates the procedures taken in developing a condition monitoring system for the motor bearing fault identification, utilizing the commonly available motor stator current and voltage. A novel intelligent diagnostic condition monitoring system has been proposed which provide continuous real time tracking of the bearing outer race defects and determines severity of the defects which can be adopted for automatic decision making. The proposed method is validated through experiments at four different defect levels under no load and full load conditions of the motor. Â© 2014 IEEE.